Eyelid Squamous Cell Carcinoma in Palembang, Indonesia: A 5-Year Retrospective Study - Zahratul Riadho; Adinda Dwivana Malika; Wardiansah (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2025)
Introduction: Eyelid squamous cell carcinoma (SCC) is a prevalent malignancy with potentially severe consequences if not detected and managed early. This study aimed to investigate the prevalence, clinical characteristics, and histopathological features of eyelid SCC patients at Dr. Mohammad Hoesin General Hospital Palembang, Indonesia, over a 5-year period. Methods: A retrospective analysis of medical records was conducted on 20 patients diagnosed with eyelid SCC between 2020 and 2024. Data on demographics, clinical presentation, tumor characteristics, and histopathological findings were collected and analyzed. Univariate analysis was performed to describe the characteristics of the study population. Correlation tests were conducted to explore the relationships between various factors and eyelid SCC. Results: The prevalence of eyelid SCC was 16.67%, with the highest incidence in 2024 (25%). The majority of patients were ≥ 50 years old (60%), with an equal distribution between males and females. Outdoor occupations (45%) and lower education levels (60% with primary education) were common characteristics. Lesions were mostly multiple (45%), >3cm in size (55%), and located on the right side (60%). Histopathological analysis revealed well-differentiated (25%) and poorly differentiated (25%) SCC as the most common subtypes. Correlation analysis revealed significant associations between age and tumor size, occupation and tumor size, education level and tumor size, smoking status and differentiation, tumor size and lymphovascular invasion, and perineural invasion and differentiation. Conclusion: Eyelid SCC in Palembang predominantly affects older individuals with outdoor occupations and lower education levels. Multiple, large, and right-sided lesions are frequent findings. Emphasis on sun protection and early detection is crucial, particularly for outdoor workers.